2017
DOI: 10.1002/aoc.3898
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐supported palladium: A hybrid system for multifunctional catalytic application

Abstract: Polymer-supported palladium was synthesized by applying a single-step wet chemical synthesis route and the resultant composite material was characterized by means of various techniques. Infrared and UV-visible spectra provided information on the chemical structure of the polymer. Microscopy techniques showed the general morphology of the polymer. The oxidation state of palladium was determined using the X-ray photoelectron spectroscopy method. The synthesized material was applied as a heterogeneous catalyst fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Literature reports have repeatedly shown that palladium nanoparticles can be efficiently supported on polymer frameworks [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Recently, Nemygina and co-workers immobilised various palladium precursors (PdCl 2 , PdCl 2 (CH 3 CN) 2 , and PdCl 2 (PhCN) 2 ) on amino-functionalized hyper-crosslinked polystyrene [ 78 ].…”
Section: Polymer Supported Palladium Nanoparticlesmentioning
confidence: 99%
“…Literature reports have repeatedly shown that palladium nanoparticles can be efficiently supported on polymer frameworks [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Recently, Nemygina and co-workers immobilised various palladium precursors (PdCl 2 , PdCl 2 (CH 3 CN) 2 , and PdCl 2 (PhCN) 2 ) on amino-functionalized hyper-crosslinked polystyrene [ 78 ].…”
Section: Polymer Supported Palladium Nanoparticlesmentioning
confidence: 99%
“…Solid supported palladium nanoparticles (Pd NPs) have widespread applications in catalysis, mostly for classical C–C coupling reactions, due to their high stability, narrow size distribution, and large surface area. 8 In this paper, Graphite Oxide (GO) was used as a solid support to anchor the Pd nanoparticles on its surface. GO contains a variety of functional groups like carboxyl, hydroxyl, and epoxy groups.…”
Section: Introductionmentioning
confidence: 99%